Hydraulic transmissivity of geocomposite confined with soils. (April 2021) - Huy Ngo, Dong; Horpibulsuk, Suksun; Buritatum, Apinun; Udomchai, Artit; Samingthong, Wisanukorn; Arulrajah, Arul; Kulariyasup, Wisit
Highlights: Develop a prototype hydraulic transmissivity, T apparatus. Investigate T of geocomposite with surrounding soil. Investigate the effect of fine content in surrounding soil on T. Investigate the effect of σv and i on T of geocomposite surrounded soil. Suggest general function to assess T of geocomposite surrounded soil. Abstract: This research investigated the effect of fine content ( F ) on the transmissivity ( T ) of geocomposite confined with single and double surrounding soil layer under various vertical stresses ( σv ) and hydraulic gradients ( i ). A prototype hydraulic transmissivity test apparatus was developed for this investigation, based on the in-plane flow rate testing device in accordance with ASTM D4716. The relationship between the T of the geocomposite and i was non-linear for both scenarios of with and without surrounding soil. The T was reduced significantly with increasing F, due to the clogging of fine particles into the channel. Non-linear relationships between generalized transmissivity and i for single and double surrounding soil conditions at various F was developed. The developed relationships assessed satisfactorily the T of geocomposites with surrounding soil at various i, σv and F, which is significant for field drainage applications.